Vaccine Side Effects Following COVID-19 Vaccination Among the Residents of the UAE-An Observational Study - Subhashini Ganesan; Subhashini Ganesan; Latifa Mohammad Baynouna Al Ketbi; Nawal Al Kaabi; Nawal Al Kaabi; Mohammed Al Mansoori; Noura Nasser Al Maskari; Mariam Saif Al Shamsi; Aysha Saeed Alderei; Hamada Nasser El Eissaee; Rudina Mubarak Al Ketbi; Noura Saeed Al Shamsi; et al. (Frontiers Media S.A., 2022)
COVID-19 vaccines have proven to be very safe in the clinical trials, however, there is less evidence comparing the safety of these vaccines in real-world settings. Therefore, we aim to investigate the nature and severity of the adverse effects reported and the differences based on the type of vaccine received. A survey was conducted among 1,878 adult (≥18 years) COVID-19 vaccine recipients through online survey platforms and telephonic interviews during March to September 2021. The factors potentially associated with the reported side effects like age, gender, ethnicity, comorbidities, and previous COVID-19 infection were analyzed based on the type of vaccine received. Differences in adverse events and the severity were compared between inactivated and mRNA vaccine recipients. The major adverse effects reported by the COVID-19 vaccine recipients were pain at the site of injection, fatigue and drowsiness, and headache followed by joint/muscle pain. The adverse effects were more common among recipients of mRNA Pfizer-BioNTech vaccine than among recipients of inactive Sinopharm vaccine with the odds ratio of 1.39 (95% CI 1.14-1.68). The average number of adverse effects reported between individuals who had received Sinopharm and Pfizer-BioNTech vaccines was 1.61 ± 2.08 and 2.20 ± 2.58, respectively, and the difference was statistically significant (p <0.001). Severe adverse effects after COVID-19 vaccinations were rare and 95% of the adverse effects reported after either an inactivated or mRNA vaccine were mild requiring no or home-based treatment. The study found that individuals less than 55 years of age, female gender, with history of one or more comorbid conditions, who had received mRNA Pfizer- BioNTech vaccine, and with history of COVID-19 infections are at higher odds of developing an adverse effect post COVID-19 vaccination compared to the others.